Seismic safety and vulnerability mitigation of school buildings - Chrysostomou, Christis; Kyriakides, Nicholas; Kappos, A.J.; Kouris, L.; Papanikolaou, V.; Dimitrakopoulos, E. G.; Giouvanidis, A. I.; Georgiou, E. (My University, 2014)
The vulnerability of existing buildings to seismic forces and their retrofitting is an international problem. The majority of structures in seismic-prone areas worldwide are structures that have been designed either without the consideration of seismic forces, or using previous codes of practice specifying lower levels of seismic forces. In Cyprus, after the three earthquakes that occurred in 1995, 1996, and 1999, the Cyprus State, acting in a pioneering way internationally, has decided the seismic retrofitting of all school buildings, taking into account the sensitivity of the society towards these structures, which house the future generation of the society. In this paper the details of the over 10 year ongoing retrofitting programme of the school buildings of Cyprus are presented and two representative school buildings are chosen for further detailed investigation as far as their retrofitting is concerned. Non-linear analysis is conducted on calibrated analytical models of the two buildings in order to derive fragility curves. These curves are used to perform benefit-cost and life-cycle analysis and evaluate the effectiveness of the retrofitting programme.
Keywords: Fragility curves; Optimum retrofit level; Schools; Seismic retrofitting